Enhancing poxvirus vectors vaccine immunogenicity - García-Arriaza, Juan (Hum Vaccin Immunother, 2014)
Attenuated recombinant poxvirus vectors expressing heterologous antigens from pathogens are currently at various stages in clinical trials with the aim to establish their efficacy. This is because these vectors have shown excellent safety profiles, significant immunogenicity against foreign expressed antigens and are able to induce protective immune responses. In view of the limited efficacy triggered by some poxvirus strains used in clinical trials (i.e, ALVAC in the RV144 phase III clinical trial for HIV), and of the restrictive replication capacity of the highly attenuated vectors like MVA and NYVAC, there is a consensus that further improvements of these vectors should be pursuit. In this review we considered several strategies that are currently being implemented, as well as new approaches, to improve the immunogenicity of the poxvirus vectors. This includes heterologous prime/boost protocols, use of co-stimulatory molecules, deletion of viral immunomodulatory genes still present in the poxvirus genome, enhancing virus promoter strength, enhancing vector replication capacity, optimizing expression of foreign heterologous sequences, and the combined use of adjuvants. An optimized poxvirus vector triggering long-lasting immunity with a high protective efficacy against a selective disease should be sought.